Cooperación científica de la Universidad Distrital Francisco José de Caldas entre los años 2011 y 2015, un acercamiento desde el Análisis de Redes Sociales (ARS) - Romero-Betancur, Jesus David (Revista Científica, 2016)
Analysis of cooperation networks formed as a result of the co-authorship of scientific texts allows a different view of space in which research activity and relationships, formal and informal, made up of researchers and constitute social capital for them develops and the institution. Based on those recorded in the SciVal platform scientific texts, which include the participation of at least one author or co-author with affiliation with the University Francisco José de Caldas, the networks made up of institutional cooperation are identified in the authorship of these texts, identifying for these and the actors who compose, modularity and the degree of cooperation, obtaining as main result, the relationship of the institutions with which it has been more relevant cooperation during the period analyzed.